A New Robust Method for Mobile Robot Multifloor Navigation in Distributed Life Science Laboratories - Ali A. Abdulla; Hui Liu; Norbert Stoll; Kerstin Thurow (Journal of Control Science and Engineering)
A new robust method is proposed for multifloor navigation in distributed Life Science Laboratories. This method proposes a solution for many technical issues including (a) mapping and localization with ceiling landmarks and a StarGazer module for achieving an accurate and low cost multifloor navigation system, (b) a new method for path planning to navigate across multiple floor environments called backbone method and embedded transportation management system, (c) elevator environment handler with the necessary procedures to interact with the elevator presenting a new approach for elevator entry button and internal buttons detection, and (d) communication system to get an expandable network; this method utilizes a TCP/IP network for the communication. Many experiments in real Life Science Laboratories proved the efficient performance of the developed multifloor navigation system in life science environment.